Spiritual Well-Being in The Experience of Indonesian Pilgrims (Systematic Review and Phenomenological Approach) - Himawanti, Izza; Aulia, Hilyati; Hidayatullah, Ahmad (Munazzama: Journal of Islamic Management and Pilgrimage, 2021)
Hajj is often synonymous with experiences of mysticism. Scientifically this experience has high Divine values. The purpose of this article is to reveal the dynamics of spiritual well-being in the experiences of Indonesian pilgrims. The qualitative method used in this study consists of two parts, namely the systematic review method and the phenomenological method. The results obtained from a systematic review analysis of spiritual well-being is a feeling of well-being between a person and God, self, social communists and the environment. This spiritual well-being will be inherent in a person's personality including life goals, religious orientation and individual existence in their social life. The results of the systematic analysis of this review serve as an objective source as a guide for researchers to explain the psychological dynamics of the mysticism phenomenon of hajj pilgrims in Indonesia. A very interesting result, this spiritual well-being can increase self-transcendence. The experience of mysticism can be implemented in a positive meaning of life. Such as gratitude, self-forgiveness, flourishing or feeling yourself one with God and the creation of mindfulness when doing worship, also positive towards the future. This experience for the pilgrims is not interpreted as merely a story in religious rituals, but more than that it becomes a transcendent in the entire domain of an individual's spiritual life. Analysis of mysticism experiences also does not focus on experiential content including the positive or negative side of experiential content, but rather focuses on the essence of appreciation and even changes in the meaning of life and individual spiritual satisfaction. The essence of the spiritual experience of the hajj pilgrimage can be an interesting and rich discussion and lesson in the study of Sufism. This research can be an entry point for the development of the concept of Hajj Mabrur at a later date.Keywords: Spiritual Well-being, Pilgrims, Hajj, Indonesia